20.9k views
0 votes
Need helpppppppppp please

Need helpppppppppp please-example-1
User Sqykly
by
5.8k points

2 Answers

3 votes
adding the two equations
3x + 6y + 3x - 6y = 36+0
6x = 36
x = 6
.
subtracting second equation from first
(3x + 6y ) - (3x-6y) =36 -0
12y = 36
y = 3
.
therefore
x = 6 and y = 3
(6,3)
User AMDI
by
6.7k points
5 votes
Short Answer A
Remark

These two equations have been set up so that all you have to do is add them in the first step.

Step One
3x + 6y = 36
3x - 6y = 0 Add them The 6ys will cancel out.
6x = 36

Step Two
Divide by 6
6x/6 = 36/6
x = 6

Step three
Use the original first equation to solve for y
3x + 6y = 36 Substitute 6 for x
3(6) + 6y = 36
18 + 6y = 36 Subtract 18 from both sides.
6y = 36 - 18
6y = 18 Divide by 6
6y/6 = 18/6
y = 3

Conclusion
The solution to these two equations is (6,3)

Answer
A

User Scolestock
by
6.3k points